Sputtering target

By using a sputtering target composed of a Cr-based alloy containing B, the metal structure of the target includes a CrB phase and a Cr single phase, it solves the problem of difficult to obtain a film with homogeneous and fine crystal structure in the prior art, and realizes high-quality film preparation suitable for an adhesion layer of a perpendicular magnetic recording medium.

CN119855939APending Publication Date: 2025-04-18SANYO SPECIAL STEEL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380068406.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-05
Filing Date
2023-10-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to obtain a homogeneous film with fine crystal structure by sputtering targets, especially in applications of adhesion layers of perpendicular magnetic recording media.

Method used

A sputtering target consisting of a Cr-based alloy containing 10.0 at% or more and 30.0 at% or less is used. The metal structure of the target includes a CrB phase and a Cr single phase. The ratio of the X-ray diffraction peak of the CrB phase with respect to the (111) plane to the X-ray diffraction peak of the Cr single phase with respect to the X-ray diffraction peak of the (110) plane is 10% or more and 80% or less.

Benefits of technology

By using the target, a homogeneous film can be formed, cracking of the target during sputtering, and is suitable for an adhesion layer of a perpendicular magnetic recording medium, providing non-magnetic, adhesion and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

Provided is a sputtering target which is mainly composed of Cr and is capable of obtaining a homogeneous thin film. The sputtering target is made of a Cr-based alloy. The Cr-based alloy contains B in an amount of from 10.0 at% to 30.0 at% (inclusive). The metal structure of the target comprises a CrB phase and a Cr single phase. The ratio of the X-ray diffraction peak of the CrB phase with respect to the (111) plane to the X-ray diffraction peak of the Cr single phase with respect to the (110) plane is from 10% to 80% (inclusive). The flexural strength of the target in a 3-point bending test is preferably 300 MPa or more. The oxygen content of the Cr-based alloy is preferably 2000 ppm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a target for sputtering for forming a metal thin film. Background Art

[0002] Sputtering is known as a method for forming a thin film. Sputtering uses a target. In sputtering, cations in plasma collide with the target. Due to this collision, atoms fly out of the target. The atoms adhere to the substrate and form a thin film.

[0003] An example of a sputtering target is disclosed in Patent Document 1 (Japanese Patent Application Laid-Open No. 2014-164780). The target disclosed in the publication is obtained by sintering a powder. The powder is composed of a Cr-based alloy. A thin film (adhesion layer) suitable for a perpendicular magnetic recording medium can be obtained from the target.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2014-164780 Summary of the invention

[0007] There is a demand for thin films to have finer crystal structures. However, the target disclosed in Patent Document 1 (Japanese Patent Application Laid-Open No. 2014-164780) cannot produce a thin film having a sufficiently fine crystal structure.

[0008] An object of the present invention is to provide a sputtering target whose main component is Cr and which can obtain a homogeneous thin film.

[0009] The sputtering target of the present invention is composed of a Cr-based alloy containing 10.0 at % or more and 30.0 at % or less of B. The metal structure of the target includes a CrB phase and a Cr single phase. The ratio of the X-ray diffraction peak of the CrB phase with respect to the (111) plane to the X-ray diffraction peak of the Cr single phase with respect to the (110) plane is 10% or more and 80% or less.

[0010] In the target, the ratio of the X-ray diffraction peak of the Cr5B3 phase with respect to the (213) plane to the X-ray diffraction peak of the Cr single phase with respect to the (110) plane is preferably 20% or less.

[0011] The target preferably has a flexural strength of 300 MPa or more in a three-point bending test.

[0012] The oxygen content of the Cr-based alloy is preferably 2000 ppm or less.

[0013] The method for manufacturing a sputtering target of the present invention comprises the following steps:

[0014] (1) A step of preparing a first powder composed of CrB;

[0015] (2) a step of preparing a second powder composed of Cr;

[0016] (3) a step of mixing the first powder and the second powder to obtain a mixed powder; and

[0017] (4) A step of pressurizing and heating the mixed powder.

[0018] In the step (2), the second powder preferably has an average particle diameter D50 of 20 μm or more.

[0019] A uniform thin film can be obtained by using the sputtering target of the present invention and the target is unlikely to crack during sputtering. DETAILED DESCRIPTION

[0020] Hereinafter, preferred embodiments will be described in detail with reference to the drawings as appropriate.

[0021] The sputtering target of this embodiment is composed of a Cr-based alloy containing B. Preferably, in the alloy, the remainder other than Cr and B is an inevitable impurity. A thin film can be formed by sputtering using the target. The thin film is suitable for various uses. A representative thin film use is an adhesion layer of a perpendicular magnetic recording medium. The adhesion layer can suppress orientation in a perpendicular magnetic recording medium.

[0022] Cr can contribute to the non-magnetic properties, adhesion and corrosion resistance of the adhesion layer. Cr has a BCC structure and has a lattice constant with a small mismatch with the (001) layer (MgO layer, etc.) stacked with the adhesion layer. Cr can suppress the orientation of the layer stacked with the adhesion layer. From these viewpoints, the Cr content in the Cr-based alloy is preferably 60at% or more.

[0023] B combines with Cr. In the target, B exists as chromium boride. It is speculated that the boride will pin the growth of grains. Thus, the target can form a thin film with a small grain diameter. In addition, B can achieve a structure without grain boundaries (amorphous). This structure is homogeneous and isotropic. This structure can contribute to the smoothness of the film. From these viewpoints, the B content in the Cr-based alloy is preferably greater than 10at%, more preferably greater than 15at%, and particularly preferably greater than 20at%. From the viewpoint of suppressing target cracking during sputtering, its content is preferably less than 30at%.

[0024] The oxygen content (quality standard) of the Cr-based alloy is preferably 2000 ppm or less. A target composed of such a Cr-based alloy is difficult to crack during sputtering. In addition, a thin film with few particles can be obtained from the target. From these viewpoints, the oxygen content is more preferably 1500 ppm or less, and particularly preferably 1000 ppm or less. Ideally, the oxygen content is less than the detection limit.

[0025] The metal structure of the target includes a CrB phase and a Cr single phase. The toughness of the Cr single phase (hereinafter referred to as the Cr phase) is extremely excellent. The toughness of the CrB phase is inferior to that of the Cr single phase. However, CrB has better toughness than other chromium borides. The metal structure including the CrB phase and the Cr single phase can suppress cracking of the target during sputtering.

[0026] Among the multiple peaks of the Cr phase obtained by X-ray diffraction, the peak P1 about the (110) plane is the largest. Among the multiple peaks of the CrB phase obtained by X-ray diffraction, the peak P2 about the (111) plane is the largest. The ratio of the X-ray diffraction peak P2 of the CrB phase about the (111) plane to the X-ray diffraction peak P1 of the Cr phase about the (110) plane is preferably greater than 10% and less than 80%. In a target with this ratio of more than 10%, B is fully dispersed and the amount of compounds with poor toughness is small. From these viewpoints, the ratio is more preferably greater than 20%, and particularly preferably greater than 25%. In a target with this ratio of less than 80%, the amount of CrB phase is not excessive. The target is difficult to crack during sputtering. From this viewpoint, the ratio is more preferably less than 60%, and particularly preferably less than 40%.

[0027] Among the multiple peaks of the Cr5B3 phase obtained by X-ray diffraction, the peak P3 about the (213) plane is the largest. The ratio of the X-ray diffraction peak P3 of the Cr5B3 phase about the (213) plane to the X-ray diffraction peak P1 of the Cr phase about the (110) plane is preferably 20% or less. In a target with this ratio of less than 20%, the amount of the Cr5B3 phase is not excessive. The target is difficult to crack during sputtering. From this point of view, the ratio is more preferably less than 10%, and particularly preferably less than 5%. Ideally, the ratio is 0%.

[0028] Peaks P1, P2 and P3 are measured by an X-ray diffraction device. The test piece for X-ray diffraction is cut from the target by wire cutting. The surface of the test piece is polished and smooth. The measurement conditions are as follows:

[0029] Test piece size: 10mm×20mm×5mm

[0030] X-ray source: CuKα rays

[0031] Scanning speed: 4° / min

[0032] 2θ: 20-80°.

[0033] From the graph obtained by the X-ray diffraction, the peak (peak intensity) is read.

[0034] The flexural strength of the target is preferably 300 MPa or more. The target is unlikely to crack during sputtering. From this point of view, the flexural strength is more preferably 400 MPa or more, and particularly preferably 500 MPa or more.

[0035] The flexural strength is measured by a three-point bending test in accordance with the "JIS Z 2511" standard. The test piece for the three-point bending test is cut from the target by wire cutting. The measurement conditions are as follows:

[0036] Test piece size: 2mm×2mm×20mm

[0037] Distance between pivot points: 10mm.

[0038] The flexural strength BS (MPa) is calculated by the following formula:

[0039] BS = 3 / 2 × P × L / (t 2 ×W)

[0040] (Where P is the load at break (kN), L is the distance between the fulcrums (mm), t is the thickness of the test piece (mm), and W is the width of the specimen (mm)).

[0041] The sputtering target can be obtained by powder metallurgy. The method comprises the following steps:

[0042] (1) A step of preparing a first powder composed of CrB;

[0043] (2) a step of preparing a second powder composed of Cr;

[0044] (3) a step of mixing the first powder and the second powder to obtain a mixed powder; and

[0045] (4) A step of pressurizing and heating the mixed powder.

[0046] By applying pressure and heating, a sputtering target can be obtained as a sintered body. The target is processed into a predetermined size and used for sputtering.

[0047] As described above, the Cr-based alloy of the target contains B. The B comes from the first powder. The first powder is composed of CrB. In other words, the first powder contains 50at% Cr and 50at% B. The target does not contain components derived from the powder composed of a single substance of B. In the target, B can be uniformly dispersed. A homogeneous thin film can be formed using the target.

[0048] Since B comes from the first powder, even the second powder having a larger particle size can achieve uniform dispersion of B. Since the second powder having a large particle size is mixed with the first powder, a target with a low oxygen content can be obtained. Specifically, a target with an oxygen content of 2000 ppm or less can be obtained by this manufacturing method. This target is not easy to crack during sputtering.

[0049] From the viewpoint of low oxygen content, the average particle diameter D50 of the second powder is preferably 20 μm or more, more preferably 40 μm or more, and particularly preferably 50 μm or more. The average particle diameter D50 is preferably 250 μm or less. The average particle diameter D50 is the particle diameter when the cumulative volume is 50% in the cumulative curve of the powder volume. The average particle diameter D50 can be measured by a laser diffraction scattering particle size distribution measuring device.

[0050] CrB of the first powder is a compound that is stable with respect to heat. CrB is unlikely to become a source of new compounds during sintering. By this manufacturing method, a target that substantially does not contain a layer other than the CrB phase and the Cr single phase can be obtained. By this manufacturing method, a target with a small amount of compounds such as Cr5B3 can be obtained. By this manufacturing method, a target in which the ratio of peak P2 to peak P1 is greater than 10% and less than 80% can be obtained. By this manufacturing method, a target in which the ratio of peak P3 to peak P1 is less than 20% can be obtained. By this manufacturing method, a target with a flexural strength of more than 300 MPa can be obtained. This target is difficult to crack during sputtering. A homogeneous thin film can be formed from the target.

[0051] Using this target, an adhesion layer of a perpendicular magnetic recording medium can be obtained by sputtering. Using this target, other thin films can be obtained by sputtering.

[0052] This specification also applies to the method for manufacturing the film. The manufacturing method includes the following steps:

[0053] (1) a step of preparing a target, the target being a Cr-based alloy containing 10.0 at % or more and 30.0 at % or less of B, the target having a metal structure including a CrB phase and a Cr single phase, wherein a ratio of an X-ray diffraction peak of the CrB phase with respect to a (111) plane to an X-ray diffraction peak of the Cr phase with respect to a (110) plane is 10% or more and 80% or less; and

[0054] (2) A step of sputtering the target.

[0055] This production method can produce a high-quality thin film. An example of such a thin film is an adhesion layer of a perpendicular magnetic recording medium.

[0056] Example

[0057] Although the effects of the sputtering targets of the examples are clarified below, the scope of the disclosure of this specification should not be interpreted restrictively based on the description of the examples.

[0058] [Example 1]

[0059] Prepare a first powder. The first powder is composed of CrB. The CrB contains 50at% of B. The average particle diameter D50 of the first powder is 10μm. In addition, prepare a second powder. The second powder is composed of pure Cr. The average particle diameter D50 of the second powder is 60μm. Put the first powder and the second powder into a V-type mixer to obtain a mixed powder. Fill the mixed powder in a carbon steel tank with a diameter of 200mm and a length of 10mm. After vacuum degassing the powder, it is made into a billet by HIP. The conditions of HIP are as follows:

[0060] Sintering temperature: 1000℃

[0061] Pressure: 120MPa

[0062] Holding time: 2 hours.

[0063] This ingot was sliced ​​to obtain a sputtering target of Example 1.

[0064] [Examples 2 to 6 and Comparative Examples 1 and 7]

[0065] Sputtering targets of Examples 2 to 6 and Comparative Examples 1 and 7 were obtained in the same manner as in Example 1 except that the mixing ratio of the first powder and the second powder was adjusted and the sintering temperature was set as shown in Table 2 below.

[0066] [Comparative Examples 2 to 6]

[0067] Sputtering targets of Comparative Examples 2 to 6 were obtained in the same manner as in Example 1 except that a specified amount of pure B powder was used instead of the first powder, a specified amount of powder composed of pure Cr with an average particle diameter D50 of 60 μm was used instead of the second powder, and the sintering temperature was set as shown in Table 2 below.

[0068] [Comparative Example 8]

[0069] The sputtering target of Comparative Example 8 was obtained in the same manner as in Example 1 except that the starting material was pure Cr powder only.

[0070] [Comparative Examples 9 to 11]

[0071] Sputtering targets of Comparative Examples 9 to 11 were obtained in the same manner as in Example 1 except that a specified amount of pure B powder was used instead of the first powder and a specified amount of fine powder consisting of pure Cr and having an average particle diameter D50 of 10 μm was used instead of the second powder.

[0072] [Oxygen content]

[0073] A test piece was cut from the target by wire cutting. The mass of the test piece was about 1 g. The surface of the test piece was polished and the oxygen content was measured using an oxygen and nitrogen analyzer (trade name "EMGA-920" manufactured by Horiba, Ltd.). The results are shown in Table 2 below.

[0074] [X-ray diffraction]

[0075] The target was subjected to X-ray diffraction using the aforementioned method. The ratio (P2 / P1) of the X-ray diffraction peak P2 of the CrB phase with respect to the (111) plane relative to the X-ray diffraction peak P1 of the Cr phase with respect to the (110) plane was calculated. The ratio (P3 / P1) of the X-ray diffraction peak P3 of the Cr5B3 phase with respect to the (213) plane relative to the peak P1 was calculated. The results are shown in Table 3 below. When the peak P2 cannot be distinguished from the noise and the ratio (P2 / P1) is less than 1%, it is displayed as "<1%". When the peak P3 cannot be distinguished from the noise and the ratio (P3 / P1) is less than 1%, it is displayed as "<1%". In the targets of Examples 1 to 6 and Comparative Examples 1 to 3, 7 and 9 to 11, no peak other than the peak P2 having a ratio of more than 1% relative to the diffraction peak P1 was observed. In the targets of Comparative Examples 4 to 6, no peaks other than the peaks P2 and P3 were observed whose ratios to the diffraction peak P1 were 1% or more.

[0076] [Measurement of area ratio]

[0077] A test piece was cut from the target by wire cutting. The size of the test piece was "10 mm × 20 mm × 5 mm". The distribution of Cr and B in the test piece was observed by EPMA (electron probe microanalysis), and the area ratio Ps of the part where B was not present was calculated. The results are shown in Table 3 below. In EPMA, the total count was 70 or more. The area ratio was calculated by dividing each count by the total count (62500). The measurement conditions of EPMA are as follows:

[0078] Range: 2mm×2mm

[0079] Beam spot size: 8μm

[0080] Number of data points: 250×250.

[0081] The results are shown in Table 2 below.

[0082] [Flexural test]

[0083] The bending strength of the target was measured by the aforementioned method. The results are shown in Table 3 below.

[0084] [Number of particles in the film]

[0085] Sputtering was performed on a target (diameter: 95 mm, thickness: 2 mm) to form a thin film. The sputtering conditions were as follows:

[0086] Substrate material: Cleaned glass

[0087] Chamber atmosphere: At a pressure of 1×10 -4 Pa and then 0.6 Pa of 99.99% pure Ar gas was injected.

[0088] Thickness of the film: 20 nm.

[0089] The film was observed using an Optical Surface Analyzer, and the number of particles with a size of 0.1 μm or more was counted. The results are shown in Table 2 below.

[0090] [Grain diameter]

[0091] The thin film was observed by TEM and the average grain size was measured. The ratio of the average grain size to the grain size of Cr in Comparative Example 1 was calculated. The results are shown in Table 2 below.

[0092]

Table 1

[0093]

[0094] Each sputtering target contains inevitable impurities in addition to the components described in Table 1.

[0095]

Table 2

[0096]

[0097] As shown in Table 2, the sputtering targets of each example have excellent flexural strength. In addition, the thin film obtained from the target has few particles and small grain diameter. Based on this evaluation result, the superiority of the sputtering target can be seen.

[0098] Thin films for various purposes can be produced using the sputtering target described above.

Claims

1. A sputtering target, comprising a Cr-based alloy containing 10.0 at % or more and 30.0 at % or less of B, wherein: The metal structure of the sputtering target includes CrB phase and Cr single phase, A ratio of an X-ray diffraction peak of the CrB phase with respect to a (111) plane to an X-ray diffraction peak of the Cr single phase with respect to a (110) plane is 10% or more and 80% or less.

2. The sputtering target according to claim 1, wherein Cr 5 The ratio of the X-ray diffraction peak of the B3 phase with respect to the (213) plane to the X-ray diffraction peak of the Cr single phase with respect to the (110) plane is 20% or less.

3. The sputtering target according to claim 1 or 2, wherein: The flexural strength of the three-point bending test is 300 MPa or more.

4. The sputtering target according to claim 1 or 2, wherein: The oxygen content of the Cr-based alloy is 2000 ppm or less.

5. A method for manufacturing a sputtering target, wherein: The following processes are available: (1) A step of preparing a first powder composed of CrB; (2) a step of preparing a second powder composed of Cr; (3) a step of mixing the first powder and the second powder to obtain a mixed powder; and (4) A step of pressurizing and heating the mixed powder.

6. The manufacturing method according to claim 5, wherein: In the step (2), the average particle diameter D50 of the second powder is 20 μm or more.

Citation Information

Patent Citations

  • Cr ALLOY FOR MAGNETIC RECORDING AND SPUTTERING TARGET MATERIAL, AND PERPENDICULAR MAGNETIC RECORDING MEDIUM USING THE SAME

    JP2014164780A